Framing Political Identity on Instagram: Personal Branding and Public Engagement in the 2024 Indonesian Presidential Election - Frizki Yulianti Nurnisya; Mohd Faizal Kasmani (Faculty of Social Sciences and Humanities Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2025)
Instagram has become a crucial platform for political communication, allowing candidates to connect with voters through visual content and interactions. This study examines the Instagram activity of six candidates in Indonesia’s 2024 Presidential Election—three presidential and three vice-presidential candidates—using content analysis to assess their campaign strategies, audience engagement, and public sentiment. The findings indicate significant variations in social media usage among the candidates. Notably, @prabowo and @gibran_rakabuming posted the least but achieved the highest engagement, suggesting that factors beyond posting frequency—such as algorithmic reach, supporter enthusiasm, and external political dynamics—played a crucial role in visibility and interaction. However, despite high engagement levels, public sentiment toward these candidates on Instagram was predominantly negative, highlighting the complex nature of digital influence. This study underscores Instagram’s dual role as both a mobilization tool and a contested space for political discourse, revealing how the interplay between engagement metrics, sentiment trends, and strategic content choices shapes political narratives in Indonesia’s evolving digital democracy.